Cybersecurity Threats and Solutions in the Current E-Healthcare Environment: A Situational Analysis (Medico Legal Update, 2019)
The need for cybersecurity measures in the field of healthcare is becoming more prescient given both theincreased sophistication of cyber criminal activity and the increased prevalence of low-security mobiledevices1. Also, hospitals have been slower to increase cybersecurity, but has become an increasing targetdue to the increased security of the financial industry2. The implementation of the Health InformationPortability and Accountability Act (HIPAA) has made patient records more portable and accessible, andcreated more opportunities for breaches1. The Health Information Technology for Economic and ClinicalHealth Act (HITECH) promoting greater implementation of electronic systems for coordination andrecords. The medical field is also becoming increasing dependent on connectivity, and people are wary ofthe threats to automated and robotic safety procedures. The threat of high dependence on technology formedical practices presents risks in and of itself, such as cases where it disrupts communication betweenhealthcare professionals, or fails to account for user failures that could be prevented with better feedbackbefore implementation. Healthcare providers are in a difficult position, trying to balance the need for quick,responsive systems for users, and need for cybersecurity measures that can slow down the computer system.In the following pages, Lewin’s field mapping approach will facilitate an analysis of the current largestcybersecurity threats and current research on the best methods of thwarting these vulnerabilities.